Microwave applicators for hyperthermia treatment of cancer: An overview - Singh S.P. (My University, 2025)
Medical applications of microwaves can be divided into three categories-i) Thermal or non-thermal effects of microwaves utilized for treatment of patients, ii) Permittivity measurement/attenuation measurement at microwave frequencies/microwave tomography utilized for diagnosis of diseases, and iii) Microwave energy and/or method utilized for treatment or diagnosis. Treatment methods based on microwave thermal effects called as Microwave Thermotherapy can be divided into following groups: Diathermy - Use of microwave to heat the tissue upto 41°C (applied in physiotherapy: e.g. in the treatment of rheumatic diseases) Hyperthermia - Use of microwave to heat the tissue in the temperature range 41-45°C (applied in Oncology in the treatment of cancer) Thermoablation/Thermodestruction - Use of microwave to heat the tissue above 45°C (applied in Urology: e.g. in the treatment of Benign Prostatic Hyperplacia (BPH)) © 2018 IEEE.